Watershed Health Assessment Using GIS and AHP Methods: Application in Stung Sen River Basin, Cambodia - Koemsreang Ka; Ty Sok; Sovatey Lim; Ilan Ich; Ratboren Chan; Layheang Song; Pinnera Ket; Chantha Oeurng (Indonesian Society of Limnology, 2022)
The watershed assessment provides information about the condition of water quality and biological integrity to identify the source of stressors and their impacts. In the present decades, different watershed assessment method has been established to evaluate the cumulative impacts of human activities on watershed health and aquatic systems. This study proposes a new approach for assessing watershed vulnerability to contamination based on spatial analysis using the Geographic Information System (GIS). and Analytic Hierarchy Process (AHP) methods. This new procedure designed to identify vulnerable zones depends on seven basic factors representing watershed characteristics: land use/land cover, sediment load, nitrate load, phosphorus load, soil type, average annual precipitation, and slope. The new watershed vulnerability assessment technique was used to create a map showing the relative vulnerabilities of specific sub-watersheds in the Sen River Basin, the largest sub-basin of the Tonle Sap Lake. The results showed a remarkable difference in watershed susceptibility between the sub-watersheds in their vulnerability to pollution. The approximate area of 10,846 km2 (76%) in the Northwest part and the long distance from the river of the study area were categorized in a range from moderate, low, and very low watershed vulnerability. However, consisting 3,341 km2 (24%) located downstream and near distance from the river were displayed as a very high and high vulnerability to pollution in the watershed. Furthermore, the results of the evaluation of the predictive reliability of the watershed vulnerability assessment method revealed that the proposed approach is suitable as a decision-making tool to predict watershed health. The process of this study indeed provides an application performance for the Sen River Basin and calls for action to sustain the water ecosystem and use.